2018
DOI: 10.1111/bcpt.13120
|View full text |Cite
|
Sign up to set email alerts
|

Meta‐analysis of the Influence of UGT Genetic Polymorphisms on Lamotrigine Concentration

Abstract: Uridine 5'-diphospho-glucuronosyltransferases (UGTs) are involved in the metabolism of lamotrigine, but whether the UGT1A4 and UGT2B7 genetic polymorphisms affect lamotrigine concentration remains controversial. Thus, the objective of this meta-analysis was to analyse the influence of UGT1A4 and UGT2B7 genetic polymorphisms on lamotrigine concentration. Through searching, screening, selection, data extraction and quantitative analyses, the influence of UGT1A4 and UGT2B7 genetic polymorphisms on lamotrigine con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…22 Also, a meta-analysis to evaluate the influence of UGT polymorphism on lamotrigine revealed that there is no significant influence of the main metabolizing enzyme UGT1A4 polymorphism on lamotrigine plasma levels. 29 It is also significant to bear in mind that During the third trimester, a decrease in the lamotrigine concentration-to-dose ratio (C/D ratio) was seen in all genotype panels and varied between 53% and 74%…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…22 Also, a meta-analysis to evaluate the influence of UGT polymorphism on lamotrigine revealed that there is no significant influence of the main metabolizing enzyme UGT1A4 polymorphism on lamotrigine plasma levels. 29 It is also significant to bear in mind that During the third trimester, a decrease in the lamotrigine concentration-to-dose ratio (C/D ratio) was seen in all genotype panels and varied between 53% and 74%…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the study used gestational week as a covariate for the clearance model, which is a better predictor of changes in plasma concentrations of lamotrigine, possibly encompassing other contributing factors, compared with other covariates, and was favored by GOF plots and bootstrap analysis 22 . Also, a meta‐analysis to evaluate the influence of UGT polymorphism on lamotrigine revealed that there is no significant influence of the main metabolizing enzyme UGT1A4 polymorphism on lamotrigine plasma levels 29 . It is also significant to bear in mind that gestational age is simpler to attain in clinical settings and permits a straightforward clinical application of the model, whereas parameters like estrogen levels and genotyping are more challenging to obtain.…”
Section: Resultsmentioning
confidence: 99%
“…4 and Table 3). The high inter-individual variability of this particular DME has been held responsible for adverse effects of lamotrigine, such as benign rashes, gastrointestinal disturbances and multi-organ failure associated with Steven Johnson syndrome 44,45 . In other reports, the reason for the observed variability has been attributed to underlying factors, such as age, gender, weight, co-medication, and state of renal and hepatic function 4650 , highlighting the possibility of population effects.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, several meta-analyses [2][3][4][5][6][7][8][9][10][11][12] have attempted to address the problem of insufficient power by pooling data from published reports on the most promising associations between pharmacogenetic variants and variations in antiseizure drug concentrations. However, a critical review shows that many of these meta-analyses either used inappropriate methods or included only subsets of all available studies (Table 1).…”
Section: Introductionmentioning
confidence: 99%